2002
DOI: 10.1182/blood.v99.5.1646
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin induces increased expression and secretion of angiopoietin-2 from human umbilical vein endothelial cells

Abstract: Angiogenesis is required for tumor growth and metastasis. It has recently been suggested that thrombin is a potent promoter of angiogenesis. We therefore examined the possibility that thrombin could be inducing the expression of angiopoietin-2 (Ang-2), necessary for remodeling. Human umbilical vein endothelial cells were incubated with or without thrombin (1 U/mL) for 1 to 24 hours and then examined for messenger RNA (mRNA) by Northern analysis. Enhanced mRNA expression (about 4-fold over baseline) was noted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
89
0
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(99 citation statements)
references
References 45 publications
3
89
0
5
Order By: Relevance
“…Furthermore, the secretion of ANG-2 stored in Weibel-Palade bodies of ECs is also tightly regulated 37 . Indeed, thrombin increased both ANG-2 synthesis in ECs and its secretion 38 . However, how ANG-2 is regulated in ECs was not clearly understood, although ANG-2 has been identified as a transcriptional target gene of FOXO1 in ECs 31,39 .…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the secretion of ANG-2 stored in Weibel-Palade bodies of ECs is also tightly regulated 37 . Indeed, thrombin increased both ANG-2 synthesis in ECs and its secretion 38 . However, how ANG-2 is regulated in ECs was not clearly understood, although ANG-2 has been identified as a transcriptional target gene of FOXO1 in ECs 31,39 .…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that vascular endothelial cells are the primary source of Ang2 (32)(33)(34)(35). High glucose increases Ang2 mRNA in HRMECs (36).…”
Section: Discussionmentioning
confidence: 99%
“…Expression profiling studies have identified endothelial cells as the primary source of Ang-2 and a dramatic transcriptional regulation of Ang-2 production upon endothelial-cell activation (Gale et al, 2002;Hackett et al, 2000;Holash et al, 1999;Huang et al, 2002;Mandriota and Pepper, 1998;Stratmann et al, 1998;Zhang et al, 2003). Correspondingly, the Ang-2 promoter contains unique positive and negative regulatory elements that control endothelial cell expression of Ang-2 .…”
mentioning
confidence: 99%